Lung-residing metastatic and dormant neuroblastoma cells - Edry-Botzer, Liat; Maman, Shelly; Sagi-Assif, Orit; Meshel, Tzipi; Nevo, Ido; Bäuerle, Tobias; Yron, Ilana; Witz, Isaac P. (The American journal of pathology, 2011)
The mechanism by which dormant tumor cells can begin growing after long periods of inactivity and accelerate disease recurrence is poorly understood. The present study characterizes dormant neuroblastoma (NB) cells, as well as metastatic cells, which reside in the same organ microenvironment. A xenograft model of human NB consisting of variants that generate nonmetastatic local tumors in the orthotopic inoculation site and variants that generate lung metastatic NB (MetNB) cells was developed in our laboratory. The present study shows that lungs of mice inoculated with nonmetastatic NB variants contain disseminated neuroblastoma (DisNB) human cells. Both DisNB and MetNB variants expressed a similar tumorigenicty phenotype in vivo, whereas the MetNB variants produced a heavy metastatic load and the DisNB variants produced no or little metastasis. A comparative in vitro characterization of MetNB and DisNB cells revealed similarities and differences. DisNB, but not MetNB cells, expressed the minimal residual disease markers PHOX2B and TH. MetNB cells demonstrated higher migratory capacity, an elevated matrix metalloproteinase (MMP) secretion, and a higher constitutive phosphorylation of extracellular signal-regulated kinase (ERK) than DisNB cells. We suggest that characteristics common to both MetNB and DisNB cells were acquired relatively early in the metastatic process and the characteristics that differ between these variants were acquired later. We hypothesize that the DisNB cells are metastasis precursors, which may progress toward metastasis under certain microenvironmental conditions.